405 ± 5 nm light emitting diode illumination causes photodynamic inactivation of Salmonella spp. on fresh-cut papaya without deterioration. (April 2017) - Kim, Min-Jeong; Bang, Woo Suk; Yuk, Hyun-Gyun
Abstract: This study evaluated the antibacterial effect of 405 ± 5 nm light emitting diode (LED) illumination against four Salmonella serovars on fresh-cut papaya and on fruit quality at various storage temperatures. To determine the antibacterial mechanism of LED illumination at 0.9 kJ/cm 2, oxidative damage to DNA and membrane lipids of Salmonella in phosphate-buffered saline solution was measured. The populations of Salmonella on cut fruits were significantly ( P < 0.05) reduced by 0.3–1.3 log CFU/cm 2 at chilling temperatures following LED illumination for 36–48 h (1.3–1.7 kJ/cm 2 ). However, at room temperature, bacterial populations increased rapidly to 6.3–7.0 log CFU/cm 2 following LED illumination for 24 h (0.9 kJ/cm 2 ), which was approximately 1.0 log lower than the number of colonies on non-illuminated fruits. Levels of bacterial DNA oxidation significantly increased, whereas lipid peroxidation in bacterial membrane was not observed, suggesting that DNA oxidation contributes to photodynamic inactivation by LED illumination. LED illumination did not adversely affect the physicochemical and nutritional qualities of cut papaya, regardless of storage temperature. These results indicate that a food chiller equipped with 405 ± 5 nm LEDs can preserve fresh-cut papayas in retail stores without deterioration, minimizing the risk of salmonellosis. Highlights: 405 nm LED illumination inactivated Salmonella on fresh-cut papaya. Antibacterial effect of LED might result from oxidation of bacterial DNA. LED illumination did not negatively influence the quality of cut papaya. LED at refrigeration could preserve cut fruits, minimizing risk of salmonellosis.